Prostate cancer detection using deep learning neural network with transfer learning approach - Badhon, Ariful Islam Mahmud; Hasan, Md. Sadman; Haque, Md. Samiul; Pranto, Md. Shafayat Hossain; Ghosh, Saurav (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.